Analisis Keterampilan Berbahasa Produktif Siswa Kelas VII Di SMPN 5 Mataram Tahun Pembelajaran 2023/2024 - Sa’diatunnisah, Sa’diatunnisah; Sudika, , I Nyoman; Intiana, Siti Rohana Hariana (Pendidikan Bahasa dan Sastra, 2023)
The research aims to describe the productive language skills of class VII G students at SMPN 5 Mataram for the 2023/2024 academic year. The population in this study were all class VII students at SMPN 5 Mataram, while the sample in this study was class VII G students totaling 34 students. This research is a type of qualitative research using descriptive methods. The data analysis method in this research goes throught several stages, namely by creating a list of raw scores, creating student ability scores, classifying student abilities, and classifying classical completion into complete and inclomplete categories. The results of research on productive language skills in the writing section showed that class VII students at SMPN 5 Mataram were categorized as incomplete with a score of >75 obtained by 19 people (55,88%), while students with a score <75 were 15 poeple (44,55%). The result of research on productive language skills in the speaking section showed that class VII students at SMPN 5 Mataram were categorized as complete with a score of >75 obtained by 30 people (88,23%), while students with a score <75 were 4 people (11,76%).